STRATEGI PERENCANAAN ANGGARAN PENDIDIKAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Alifha Nurfidia; Eva Maulina; Novita Asriningrum; Vivi Alfiyah; Harsono; Suyatmini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the mismatch between educational budget allocation and learning needs in elementary schools, which may affect learning quality. This study aimed to analyze educational budget planning strategies in improving learning quality at the elementary school level. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and document analysis involving principals, treasurers, teachers, and school committee members involved in budget planning and implementation. Data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that budget planning was conducted through learning needs identification, priority setting, stakeholder participation, and budget evaluation. Needs-based and participatory budget planning supported the provision of learning facilities, teacher professional development, and instructional innovation. However, the implementation faced several challenges, including limited financial resources, policy changes, and managerial constraints. The study concludes that effective budget planning strategies contribute to improving learning quality in elementary schools.